Analisis Perbandingan Kinerja Keuangan Perusahaan Sektor Pariwisata Sebelum dan pada Masa Pandemi Covid-19 Terhadap Risiko Kebangkrutan (Studi Kasus Pada Sub Sektor Perusahaan Pariwisata, Perhotelan, Restoran dan Kapal Pesiar yang Terdaftar di BEI Periode 2018-2021) - Rindi Silvine Aprilia; Risal Rinofah; Pristin Prima Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine differences in the financial performance of companies in the tourism sector before and during the Covid-19 pandemic and to determine the effect of financial performance as seen from the profitability ratios, liquidity ratios and solvency ratios on the risk of company bankruptcy. The sample used in this study is tourism sector companies listed on the IDX for the 2018-2021 period. The data collection method used a purposive sampling method and obtained 30 companies with a total of 120 data. The analysis technique used to determine differences in financial performance is using the Wilcoxson Signed Ranks Test. Meanwhile, to test the effect of financial performance on bankruptcy risk using multiple linear regression analysis techniques. The results of the different tests using the Wilcoxson Signed Ranks Test are that there is no difference in current ratio and debt to asset ratio before and during the Covid-19 pandemic, while in other ratios there is no difference in financial performance before and during the the covid-19 pandemic. The results of the influence test using the multiple linear regression analysis technique stated that the Quick Ratio (QR) before the Covid-19 pandemic had an effect on bankruptcy risk, while other ratios had no effect on bankruptcy risk before the pandemic. During the Covid-19 pandemic the ratios of ROA, ROE and DER did not affect the risk of company bankruptcy, while the ratios of CR, QR and DAR had an effect on bankruptcy risk.